2017
DOI: 10.3390/jimaging3040058
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Imaging of Laser Melted SS316 Test Objects with Spatially Resolved Small Angle Neutron Scattering

Abstract: Abstract:A novel neutron far field interferometer is explored for sub-micron porosity detection in laser sintered stainless steel alloy 316 (SS316) test objects. The results shown are images and volumes of the first quantitative neutron dark-field tomography at various autocorrelation lengths, ξ. In this preliminary work, the beam defining slits were adjusted to an uncalibrated opening of 0.5 mm horizontal and 5 cm vertical; the images are blurred along the vertical direction. In spite of the blurred attenuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…A far-field grating interferometer 17 20 and single absorbing grating 21 that can alter ACL based on the period of the moiré pattern have been studied by directly reading the pattern using such detectors without using analyzer gratings, which achieves an ACL range from tens of nanometers to several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…A far-field grating interferometer 17 20 and single absorbing grating 21 that can alter ACL based on the period of the moiré pattern have been studied by directly reading the pattern using such detectors without using analyzer gratings, which achieves an ACL range from tens of nanometers to several micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to acquire fabrication process-related microstructural information in connection with UHV performances, a non-invasive morphological and microstructural study of the MACHINA metal AM beam exit snout was performed using a combination of X-ray and Neutron Tomography (Maire and Withers 2014;Vontobel et al 2006). Over the years, these techniques have been used on metal AM components (see for example (Thompson et al 2017(Thompson et al ,2016Sacco and Moon 2019;Leung et al 2018; du Plessis 2020) for X-ray CT and (Watkins et al 2013;Tremsin et al 2016;Cakmak et al 2018;Brooks et al 2018;Rahman et al 2019;Hönnige et al 2018) for Neutron Tomography) and less frequently together (see for example (Watkins et al 2013)), since they can provide crucial information, as indicated e.g. in Perry et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in far-field phase-grating moiré interferometry extends phase-grating neutron interferometry to high intensity sources of thermal neutrons, showing promise for impactful long-path-length experiments and providing new methods of characterizing materials by scanning the autocorrelation length over many orders of magnitude. [21][22][23][24][25] This novel technique has proven to be advantageous over other neutron interferometry setups in terms of broader wavelength acceptance and less stringent alignment requirements. However, an important measure of interferometer performance is its contrast, or interference fringe visibility, defined by the amplitude of the interference pattern divided by the mean intensity.…”
Section: Introductionmentioning
confidence: 99%